Smart Education and e-Learning 2018 - Uskov, Vladimir L.; Howlett, Robert J.; Jain, Lakhmi C.; Vlacic, Ljubo (Smart Innovation, Systems and Technologies,, 2019)
This book features the contributions presented at the 5th International KES Conference on Smart Education and e-Learning, which took place in Gold Coast, Australia, June 20-22, 2018. The peer-reviewed papers are grouped into several interconnected parts: Part 1 - Smart Education: Systems and Technology, Part 2 - Smart Pedagogy, Part 3 - Smart Education: Case Studies and Research, and Part 4: Sustainable Learning Technologies: Smart Higher Education Futures. Smart education and smart e-learning are emerging and rapidly growing areas with the potential to transform existing teaching strategies, learning environments, and educational activities and technology in the classroom. Smart education and smart e-learning focus on enabling instructors to develop new ways of achieving excellence in teaching in highly technological smart classrooms, and providing students with new opportunities to maximize their success and select the best options for their education, location and learning style, as well as the mode of content delivery. This book serves as a useful source of research data and valuable information on current research projects, best practices and case studies for faculty, scholars, Ph.D. students, administrators, and practitioners - all those who are interested in smart education and smart e-learning.